The β-triketone, nitisinone, kills insecticide-resistant mosquitoes through cuticular uptake - Zachary Thomas Stavrou-Dowd; George Parsons; Clair Rose; Faye Brown; Rosemary Susan Lees; Álvaro Acosta-Serrano; Lee Rafuse Haines (Parasites & Vectors)
Abstract Background Insecticide resistance in disease-transmitting arthropods of agricultural, veterinary, and public health significance poses a significant threat to vector control programs worldwide. Previous studies demonstrated that blood-feeding arthropod vectors experience high mortality when ingesting blood containing inhibitors of 4-hydroxyphenylpyruvate dioxygenase (HPPD), the second enzyme in tyrosine metabolism. This study investigated the mosquitocidal efficacy of HPPD inhibitors from the β-triketone class of herbicides against both susceptible and pyrethroid-resistant strains of three major disease vector species, including mosquitoes that transmit historical diseases such as malaria, reemerging infections such as dengue and Zika, and emerging viral threats such as Oropouche and Usutu viruses. Methods Four HPPD inhibitors (nitisinone, mesotrione, sulcotrione, and tembotrione) were screened using glass plate tarsal bioassays at 125 mg/m2 against bloodfed Anopheles gambiae s.s. Kisumu. Nitisinone was selected for evaluation against susceptible and pyrethroid-resistant strains of An. gambiae s.s. Kisumu, An. gambiae s.l. Tiassalé 13, An. coluzzii VK7 2014, Culex quinquefasciatus Muhezha, and Aedes aegypti New Orleans. Mosquitocidal activity was assessed using glass plate tarsal contact bioassays, topical application assays (0.0001% to 1% w/v), and modified Centers for Disease Control and Prevention (CDC) bottle bioassays (0–30 μg per bottle). Female mosquitoes aged 3–5 days were bloodfed within 1 h before exposure. Mortality was recorded at 30 min and 24, 48, and 72 h post-exposure under controlled conditions. A total of 3 biological replicates of 30 mosquitoes per treatment were used. Results Only nitisinone, and not mesotrione, sulcotrione, or tembotrione, exhibited significant mosquitocidal activity when bloodfed mosquitoes were exposed to treated surfaces. No significant differences in susceptibility to nitisinone were observed between insecticide-susceptible An. gambiae and strains harboring multiple insecticide-resistance mechanisms. The compound demonstrated consistent efficacy across all three mosquito species tested, indicating broad-spectrum activity against major disease vectors. Conclusions This study demonstrates that nitisinone exhibits a novel mode of action distinct from current Insecticide Resistance Action Committee (IRAC) classifications by specifically targeting blood digestion processes. Its efficacy against resistant strains and potential for integration into existing vector control interventions, such as treated bednets and indoor residual spraying, highlight nitisinone as a promising candidate for expanding strategies against malaria, dengue, Zika, and other emerging viral diseases. Graphical Abstract